Clavicular hook plate fixation for acromioclavicular joint injuries and lateral clavicle fractures: a case series of 13 military patients - Amarasekara, Chaminda; Wijedasa, Chinthaka P.; Gunasekara, Amaila P. (International Surgery Journal, 2026)
Acromioclavicular joint (ACJ) injuries and lateral clavicle fractures are common among military personnel due to high-energy trauma sustained during training, sports, and operational activities. Reliable fixation is essential to restore function and enable early return to duty. We present a case series of 13 serving naval patients treated with clavicular hook plate (CHP) fixation between September 2012 and November 2018 at the Navy General Hospital, Colombo, Sri Lanka. Inclusion criteria were Rockwood Type III/IV ACJ injuries or lateral clavicle fractures. Functional outcomes were assessed using the Disabilities of the arm, shoulder, and hand (DASH) score. The mean patient age was 32.8 years (range: 21-41). Mechanisms of injury included road traffic accidents (53%), accidental falls (31%), and sports injuries (15%). Diagnoses comprised Rockwood type III ACJ injuries (79%), lateral clavicle fractures (14%), and Rockwood type IV injuries (7%). The mean interval from injury to surgery was 14 weeks. At follow-up, 69% achieved excellent outcomes (DASH<2), while 23% reported moderate impairment. One patient developed ACJ separation following plate removal. This case series demonstrates that clavicular hook plate fixation combined with structured rehabilitation is effective for Rockwood Type III and lateral clavicle injuries in young, active military personnel. Early intervention facilitates favorable recovery, though implant-related complications highlight the need for careful monitoring.